The Communication Network Pattern of the Tourism Merchant Association in Disseminating New Normal Information - Wahyu Illahirobbi; Ainur Rochmaniah (Indonesian Journal of Cultural and Community Development, 2022)
The new normal is a new policy implemented by the government in collaboration with the Pecalukan Tourism Trade Association to reduce the number of soaring COVID-19 cases. This ongoing transition towards a new normal is an implication of various policies and regulations during the COVID-19 emergency response period. The purpose of this study was to determine the pattern of communication networks formed in the association in disseminating information. This study uses descriptive quantitative research methods with communication network analysis techniques, while the sampling technique is the snowball sampling technique. Data collection techniques using questionnaires through interviews. The research is the first pattern of communication network structure that is formed by communication networks of all channels. The two roles of the communication structure are as follows: Click, Gate Keeper, Bridge, and Opinion Leader. The three communication networks were found by 4 clicks. There are 7 opinion leaders in the communication network who have an important role in influencing and increasing the participation of community members.